Programming Robots with ROS: A Practical Introduction to the Robot Operating System : - Quigley, Morgan (O'Reilly Media, 2016)
Want to develop novel robot applications, but don’t know how to write a mapping or object-recognition system? You’re not alone, but you’re certainly not without help. By combining real-world examples with valuable knowledge from the Robot Operating System (ROS) community, this practical book provides a set of motivating recipes for solving specific robotics use cases.